Visual wound-assessment by population groups with different educational backgrounds - Körber, A.; Cesko, E.; Dissemond, J. (Phlebologie, 2009)
The documentation of chronic wounds is presently carried out by a number of different occupational groups, partly with considerable differences in knowledge. Besides testing the quality of judgement, the aim of our clinical study was therefore also to test the reproducibility of the visual wound assessment by population groups with different educational backgrounds. Participants, material, methods: The subjects, belonging to population groups; experts, doctors, nursing services, hospital nursing staff and laities, were required to assess all relevant parameters of wound assessment at two different points in time. A newly developed digital, colorimetric wound documentation system was used as an objective reference. Results: The wound assessment was evaluated both intra-individually as well as inter-individually. A noticeably better quality of assessment of objective parameters, such as length, breadth, surface, wound stage and wound infection, was shown by the population groups with previous experience, both in the single and two phase analysis. The wound coating assessments of all population groups were equally inaccurate at both points in time. Conclusion: Consequently, it may be concluded that it is not possible to attain sufficient, reliable and adequate wound documentation without technical aids, for example a digital photo documentation. Especially the assessment of the wound surface and coating is of an insufficient standard, whether carried out at a specific point in time or in a sequence.
Keywords: Wound documentation; wound healing; leg ulcers; chronic wounds